Regeneration of five Combretaceae species along a latitudinal gradient in Sahelo-Sudanian zone of Burkina Faso - (:unkn) unknown (My University, 2010)
Seedling density and the regeneration mechanisms of five tree species, Anogeissus leiocarpa, Combretum aculeatum, Combretum micranthum, Combretum nigricans, and Pteleopsis suberosa were investigated in relation to latitudinal gradient across the Sahelo-Sudanian zone of West Africa.* Data were collected on 461 quadrats (2m × 5m) laid out every 30 m on transect lines through Combretaceae communities at four latitudinal positions. Regeneration mechanisms were determined by excavating the below ground root system and assessing basal and aerial sprouts.* The results showed a significant species × latitudinal position effect on the total density of seedling populations, and the density of single- and multi-stemmed individuals (p < 0.001). C. aculeatum and C. micranthum were abundant in the North-Sahelian sector, C. nigricans and P. suberosa in the Sudanian sector and A. leiocarpa across a wide range from the South-Sahelian to South-Sudanian sectors. In general, 58% of the seedlings were regenerated asexually (as coppice, water sprout, layer, and root sucker) while 42% were sexual recruits (as true seedling and seedling sprouts). The proportion of vegetatively propagated seedlings increased with increasing latitude for all species except C. micranthum, for which a clear decreasing trend was observed. The relative importance of the different regeneration mechanisms varied among species: seedling sprouts were important for A. leiocarpa, C. aculeatum and C. nigricans, coppice for C. micranthum and sucker for P. suberosa* The significant interaction observed between species and latitudinal position highlights the importance of accurate species-site matching to ensure successful restoration of degraded areas in the Sahelo-Sudanian zone. Inter-species differences in regeneration mechanism could be related to their biology and ecological adaptation to the site-specific biotic and abiotic factors.
Keywords: African Research